Siria Pérez Fabas: Well-known Head of Nursing - Maritza Cardosa Samón; Clara Zapolta Moré; Yanexi Ramirez Silva (Universidad de Ciencias Médicas de La Habana, 2018)
To pay tribute to the 55th anniversary of the death of doctor Enrique Cabrera, "Enrique Cabrera" General Teaching Hospital highlights in its historical site the work carried out by some well-known and prestigious personalities of the institution such as the work of Bachelor of Nursing Syria Pérez Fabas who has dedicated her life to assistance, administration and teaching.  She has been excellent as a health care provider who has given a careful care, demonstrated a great vocation of service, and developed leadership in health services. She has been the guide and teacher of many professionals of the health sector, an exceptional nurse dedicated to her profession, and an active promoter for the formation of specialists and research development in our country.  Pérez Fabas was credited with multiple national and international recognitions; she gave memorable administrative recommendations, building human quality in each worker that accompanied her in diverse teachings to nursing professionals during 18 years of her leadership. At present, she continues working in the formation of new generations in the Preparatory Faculty of Cojímar. Keywords: Nursing, nursing supervision, Administration of Health Care Services, Teaching, Continuous Education in Nursing.